Memória e criação artística: a imagem fotográfica como indutora de processos pedagógicos cênicos no espaço escolar - Sabrina Soares Aguiar (2023)
The present work addresses the possibilities for teaching and learning theater and scenic creation in the school environment, based on memories and photographic records. It seeks to reflect on how photography can be used as an artistic and pedagogical stimulus for teaching theater. Additionally, a didactic and pedagogical material is proposed that utilizes improvisation games based on memories and photographic narratives, with the aim of contributing to the process of teaching and scenic creation in Elementary Education.